Psychometric Properties of the Persian Version of Modified Short Form of Changes in Outlook Questionnaire Following Disaster for Injured Athletes - Rokhsareh Badami (Vesnu Publications, 2020)
Introduction: This study addresses the psychometric properties of the Persian version of the Changes in Outlook Questionnaire (CiOQ) questionnaire following disaster for injured athletes. CiOQ has been designed to measure both positive and negative changes following disaster. The aim of this study is to translate the short form of the questionnaire (CiOQ-S) into Persian and examine its validity and reliability in a sample of the injured athletes. Materials and Methods: The 10-item English version of CiOQ was translated into Persian and completed along with the Hospital Anxiety and Depression Scale (HADS) in a sample of injured athletes deprived of competition (n = 207). Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were used to evaluate the construct validity. In addition, the Cronbach's alpha and split-half coefficients were applied to measure reliability. Moreover, the convergent validity was measured using the Pearson's correlation coefficient. Results: The Persian version of CiOQ demonstrated a similar factor structure to that of the English version, high internal consistency, and convergent validity with measures of anxiety and depression support. The reliability obtained using the Cronbach's alpha and split-half coefficients were higher than 0.7 for both positive and negative changes. There was a negative correlation between positive change and depression (P < 0.001). However, there was a positive correlation between negative changes with anxiety and depression (P < 0.001). Conclusion: Data indicated that the the Persian version of CiOQ is a reliable and valid measure for assessing positive and negative changes following an adversity.